Sentiment Analysis of ChatGPT Tweets Using Transformer Algorithms - Sugeng Winardi; Mohammad Diqi; Arum Kurnia Sulistyowati; Jelina Imlabla (Universitas Wahid Hasyim, 2023)
This study explores the application of the Transformer model in sentiment analysis of tweets generated by ChatGPT. We used a Kaggle dataset consisting of 217,623 instances labeled as